Employing arynes for the generation of aryl anion equivalents and subsequent reaction with aldehydes - Gaykar, Rahul N.; Bhunia, Anup; Biju, Akkattu T. (Journal of Organic Chemistry, 2018)
Arynes are highly reactive intermediates, which are utilized for the electrophilic arylation of various X-H bonds (X = O, N, S etc.). Herein, a new synthetic strategy is demonstrated, where arynes are converted into aryl anion equivalents by treatment with phosphines and a base. The addition of phosphines to arynes form the phosphonium salts, which in the presence of a carbonate base generates the aryl anion equivalent. Subsequent addition of the aryl anions with aldehydes afforded the secondary alcohols.